The case of "RTP" and "La tribuna libre del pueblo": Media, mediations and constitution of collective identities in popular sectors - Choque Aldana, Marlene (1998)
The role of the mass media in the contemporary politics of Latin American societies has been little studied from the social sciences. Most research to date has prioritized the study of "classical" political institutions or actors such as parties, the state, or generic issues such as democratic transition processes, authoritarianism, or (neo) populism. The objective of this paper is to reflect on the new space and the new roles that the mass media are assuming and fighting in Latin American societies, in a context of accelerated institutional transformations and social relations.